Improved Measurement of Absolute Hadronic Branching Fractions of the Ds+ Meson - Collaboration, CLEO; Onyisi, P; Bonvicini, G; Cinabro, D; Smith, M; Zhou, P; Naik, P; Rademacker, J; Edwards, K; Briere, R; Vogel, H; Rosner, J; et al. (2013)
The branching fractions of Ds meson decays serve to normalize many measurements of processes involving charm quarks. Using 586 pb^-1 of e+ e- collisions recorded at a center of mass energy of 4.17 GeV, we determine absolute branching fractions for 13 Ds decays in 16 reconstructed final states with a double tag technique. In particular we make a precise measurement of the branching fraction B(Ds -> K- K+ pi+) = (5.55 +- 0.14 +- 0.13)%, where the uncertainties are statistical and systematic respectively. We find a significantly reduced value of B(Ds -> pi+ pi0 eta') compared to the world average, and our results bring the inclusively and exclusively measured values of B(Ds -> eta' X)$ into agreement. We also search for CP-violating asymmetries in Ds decays and measure the cross-section of e+ e- -> Ds* Ds at Ecm = 4.17 GeV.